2016
DOI: 10.1016/j.ultsonch.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound processing to enhance drying of cashew apple bagasse puree: Influence on antioxidant properties and in vitro bioaccessibility of bioactive compounds

Abstract: The present study has evaluated the effects of power ultrasound pre-treatment on air-drying and bioactive compounds of cashew apple bagasse. The sonication induced the disruption of cashew bagasse parenchyma, which resulted in lower resistance to water diffusion, less hysteresis, and increased rehydration rate. The processing did not affect the lignocellulose fibers or the sclerenchyma cells. For sonicated samples, water activity reached values below 0.4, after 2h of drying, which is appropriate to prevent bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 42 publications
1
39
0
Order By: Relevance
“…Sonication improved the quality of dried cashew apple bagasse, with an important enhancement (400%) of the total phenolic bioaccessibility (Fonteles et al, 2016).…”
Section: Ultrasounds Treatmentmentioning
confidence: 99%
“…Sonication improved the quality of dried cashew apple bagasse, with an important enhancement (400%) of the total phenolic bioaccessibility (Fonteles et al, 2016).…”
Section: Ultrasounds Treatmentmentioning
confidence: 99%
“…Numerous studies have been reported a higher mass transfer during extraction (Goula, ; Jovanovic‐Malinovska, Kuzmanova, & Winkelhausen, ; Zhao, Shi, Yang, & Mao, ) and drying (do Nascimento, Mulet, Ascheri, de Carvalho, & Cárcel, ; Fonteles et al, ; Ozuna, Cárcel, Walde, & Garcia‐Perez, ; Rodríguez et al, ). The enhancement in extraction is related to the mechanically disruption of the cell walls and reduction in the particle size (Rodrigues & Pinto, ).…”
Section: Introductionmentioning
confidence: 99%
“…From products derived from cashew apple, juice is the one presenting the largest market and its extraction generates a residue called bagasse or cashew fiber, which represents 20 to 40% of the cashew apple weight (ROCHA et al, 2014;ALBUQUERQUE et al, BIASOTO et al, 2015, FONTELES et al, 2016. Cashew fiber is traditionally directed to animal feed (SIQUEIRA, BRITO, 2013) or even used as a substrate for the production of co-products such as ethanol and xylitol (ROCHA et al, 2014;ALBUQUERQUE et al, 2015;COSTA et al, 2015).…”
Section: Introductionmentioning
confidence: 99%